DEVELOPMENT OF SNAKE LADDER LEARNING MEDIA BASED ON LOCAL WISDOM IN INDONESIAN THIRD GRADE ELEMENTARY SCHOOL SUBJECTS - Arina Faza Zulfa; A Syachruroji; Rina Yuliana (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
wisdom in Indonesian language lessons in class III elementary school and to see the feasibility of snake ladder learning media products based on local wisdom in the eyes of Indonesian language lessons in class III elementary school that is being developed worthy of expert. This study was conducted in Karang Tumaritis Elementary School with research subjects in class III with 20 students in limited trials. The type of research used in the development research (Research and Development) of Borg and Gall which issued from Sugiyono consisted of 6 stages. The instrument used was a questionnaire for expert validation and student response. The result of the shielding test by experts on the quality of the media that can be used in very large calculations is 88%. The results of the limited trial on students towards the media really correspond to the percentage of 93.33%. The results of the study can be concluded that the media developed are very effective in the process of learning Indonesian. Keywords: snake ladder media, local wisdom, Indonesian